THINK TALK WRITE MODEL ON ANALYSIS ABILITY OF ELEMENTARY SCHOOL STUDENTS: EXPERIMENTAL STUDY - Mu’alifah; Rarasaning Satianingsih; Via Yustitia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Analytical skill is the ability to describe the materials into parts or components that are more structured and easier to understand. Currently the students are still less than optimal in mastering the concepts of teaching materials. Mastery of concepts related to the ability of thinking related to the analytical skills of students. Think Talk Write (TTW) models can be used as an alternative to improve the analysis because this model is more emphasis on specialized structures designed to affect the pattern of interaction of students and has a goal to foster students' analytical skills. This study aims to determine the analytical skills of fourth grade students who were taught by using TTW models. This research was a quantitative research Quasi-Experimental Design with Posttest-Only Control Design. The population in this study were all students of class IV SDN Ketabang Surabaya academic year 2019/2020. Data were analyzed using normality test, homogeneity test, a balance test and t test aided SPSS 22. The results showed that the analytical skills of fourth grade students who were taught by using the TTW model significantly better than the students who were taught by using a contextual model SDNKetabang Surabaya.